RF and DC Power Combining for Rectenna Arrays: Layout Approach and Technical Analysis - Vinicius S. Silva; Renan Diniz; Humberto Pereira da Paz; Ivan Roberto Santana Casella; Mustapha C. E. Yagoub; Carlos Eduardo Capovilla (IEEE Access, 2025)
Radio Frequency Energy Harvesting (RFEH) has become a promising alternative for powering low-power devices in wireless networks. However, the low power spectral density values normally available in the environment limit its application. So, one of the possible strategies to overcome this problem can be the use of antenna arrays in rectennas, to increase the RF power available at rectification input. However, from an RFEH perspective, the use of arrays presents a new challenge to optimization, choosing the domain in which the power combination (RF or DC) is performed. In this context, this work aims to compare array design strategies in an RFEH context, by analyzing the DC performance of these arrays at 2.4 GHz. The spatial limitation, which ensures fairness in comparison, is defined by the final dimensions of the rectenna composeb by $2× 1$ antenna array with the best RF power performance.